How to run and win in local elections (Women in Politics Program of the Center for Legislative Development, 1997)
Gives detailed and concise instructions on how to run in the local elections in the Philippines. It is like a simplified version of the election code of the Philippines. It also presents suggestions on assessing who will run, having a successful campaign and even delivering a speech.